748. The Impact of a Positive Respiratory Viral Panel Among Hospitalized Adult Patients with Negative Rapid Influenza Testing at an Academic Tertiary Care Facility: A-matched Cohort Study. (26th November 2018) - Ciccone, Emily; Kinlaw, Alan; Chundi, Vahini; Miller, Melissa; Weber, David; Juliano, Jonathan; Jhaveri, Ravi; Willis, Zachary; ,
Abstract: Background: Multiplex nucleic acid amplification assays (NAATs) are increasingly used to evaluate respiratory illnesses. Viral diagnosis has the potential to change clinical management and, specifically, decrease antibiotic use. However, the assays are expensive, and their effect on clinical management is unknown. This study evaluated the incremental impact of a multiplex respiratory viral panel after negative rapid influenza testing. Methods: We completed a retrospective review of all adult patients with respiratory viral panel (RVP; GenMark) and/or rapid influenza or RSV/influenza PCR tests (PCR; Cepheid Xpert) collected within 48 hours of admission to non-ICU, inpatient units from September 1, 2015 to April 15, 2016. We matched hospitalizations with a positive RVP simultaneously with or following negative PCR testing (PCR−RVP+) 1:1 with patient encounters with negative rapid PCR testing only (PCR−). Matching of the referent PCR-group occurred without replacement based on age (±10 years), sex, race, season of testing (±50 days), and any respiratory viral test in the prior 30 days. The primary outcome was a change in management, defined as antimicrobial de-escalation (discontinuation, switch from intravenous to oral administration, and/or narrowing of spectrum), antiviral initiation, and/or change in isolation precautions. Results: During the study period, there were 153 PCR−RVP+ patient encounters and 524 with PCR− testing only from which we identified 134 matched pairs. In the matched cohort, the median age was 60 years (IQR: 41–71), 47.8% were female, and 34.3% were non-White. Respiratory viral testing was associated with management change in 3.7% of PCR− and 23.9% of PCR−RVP+ patients (risk difference 20.1%; 95% CI 12.2–28.0%). Antimicrobial de-escalation did not occur after testing for any PCR- patients but did occur for 15.7% of PCR−RVP+ patients (95% CI 9.5–21.8%). Conclusion: Among patients with negative rapid influenza testing, a subsequent or simultaneous positive RVP was associated with a higher frequency of antibiotic de-escalation. This suggests multiplex NAATs could play a role in improving antimicrobial stewardship in the setting of respiratory illness. Disclosures: M. Miller, GenMark: Investigator, Research support. R. Jhaveri, GenMark: Investigator, Research support.